Etično presojanje študentov farmacije na primerih etičnih dilem iz lekarniške dejavnosti - Ošlak, Maša (Farmacevtski vestnik, 2024)
Intuitively, the application of ethical principles to pharmacy seems clear. The Code of Pharmacy Deontology and the Code of Pharmacy Ethics of the members of the Slovenian Pharmaceutical Society guide the ethical conduct of Slovenian pharmacists, and the ethical competence of pharmacy students is based on their familiarity with them and the knowledge they acquire during the study process and through practical training in learning centres. The aim of our research was to identify the ethical frames of reference developed by pharmacy students through the application of ethical principles based on the solution of scenarios depicting ethical dilemmas. Through a literature review, we developed appropriate content for a questionnaire for an online survey of a purposive sample of pharmacy students. The ethical principles of beneficence, non-maleficence, autonomy, honesty, confidentiality and justice are reflected in students’ responses to examples of ethical dilemmas and can be used to evaluate ethically acceptable behaviour. We pro¬pose to restructure the codes currently designed for professional practice to provide a source of principles and a consistent approach to resolving ethical dilemmas.
Keywords: ethical dilemmas; ethical judgement; ethical principles; etična načela; etične dileme; etično presojanje; Etika; Farmacevti; Lekarniška dejavnost; lekarniška praksa; pharmacy practice; pharmacy students; študenti farmacije